Roles and mechanisms of CircRNAs in ovarian cancer - Liu, Min; Cao, Siyu; Guo, Ziyi; Wu, Zong; Meng, Jiao; Wu, Yong; Shao, Yang; Li, Yanli (Frontiers in Cell and Developmental Biology, 2022)
Ovarian cancer (OC) is one of the female malignancies with nearly 45% 5-year survival rate. Circular RNAs (circRNAs), a kind of single-stranded non-coding RNAs, are generated from the back-splicing of cellular housekeeping noncoding RNAs and precursor messenger RNAs. Recent studies revealed that circRNAs have different biological function, including sponging miRNAs, encoding micropeptides, regulating stability of cytoplasmic mRNAs, affecting transcription and splicing, via interacting with DNA, RNA and proteins. Due to their stability, circRNAs have the potential of acting as biomarkers and treatment targets. In this review, we briefly illustrate the biogenesis mechanism and biological function of circRNAs in OC, and make a perspective of circRNAs drug targeting immune responses and signaling pathways in OC. This article can provide a systematic view into the current situation and future of circRNAs in OC.